Time to change implementation units for mass drug administration against schistosomiasis in Uganda: Evidence from Communities levels data validation and its implication in planning - Moses Adriko; Benjamin Tinkitina; Moses Arinaitwe; Edridah M. Tukahebwa; Alfred Mubangizi; Jorge Cano Ortega; Honorat Zoure; Pauline N. Mwinzi; Boniface Kinvi; Amadou Garba Djirmay; Sammy Njenga; Humphrey D. Mazigo (Parasite Epidemiology and Control)
Uganda started implementing mass drug administration against schistosomiasis in 2003, with district used as an implementation unit. This resulted into misclassification of communities into wrong risk levels, under-or-over treatment and over request of praziquantel (PZQ) drugs. The objective of the current study was to reviewing the community data available at World Health Organization/ESPEN database to understand the status of schistosomiasis and identify pockets with infection. The decision tree assessment tool was used to analyzed schistosomiasis epidemiological data of 7501 communities. Before validation, the schistosomiasis endemicity status of 79 % of communities was not known. After validation, 58.6 %, 22.6 % and 16.3 % of communities were not endemic, had low and moderate endemicity status. Of 2362 communities classified having high endemicity using a district as implementation unit, 41.6 %, 12.7 % and 17.3 % of them were not endemic, had low and moderate endemicity, while only 22.7 % had high endemicity. Using the new treatment guidelines, 2,875,006 school aged children were adequately treated, 18,235 were under-treated and 2,250,013 were over treated. The results show a considerable change in endemicity status when communities were used as an implementation unit compared to district. Thus, the country control programme is recommended to use communities as implementation unit.